Beispiel Nr: 03
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -3x^3+24 =0\\ \\ \textbf{Rechnung:} \\\\-3x^3+24=0 -3x^3+24 =0 \qquad /-24 \\ -3x^3= -24 \qquad /:\left(-3\right) \\ x^3=\displaystyle\frac{-24}{-3} \\ x=\sqrt[3]{8} \\ x=2 \\ \text{Polynomdivision:}2\\ \small \begin{matrix} (-3x^3&&&+24&):( x -2 )=-3x^2 -6x -12 \\ \,-(-3x^3&+6x^2) \\ \hline &-6x^2&&+24&\\ &-(-6x^2&+12x) \\ \hline &&-12x&+24&\\ &&-(-12x&+24) \\ \hline &&&0\\ \end{matrix} \\ \normalsize \\ -3x^{2}-6x-12 =0\\ x_{1/2}=\displaystyle\frac{+6 \pm\sqrt{\left(-6\right)^{2}-4 \cdot \left(-3\right) \cdot \left(-12\right)}}{2\cdot\left(-3\right)}\\ x_{1/2}=\displaystyle \frac{+6 \pm\sqrt{-108}}{-6}\\ \text{Diskriminante negativ keine Lösung} \\ \underline{x_1=2; \quad1\text{-fache Nullstelle}} \\$